2022
DOI: 10.21776/ub.jitek.2022.017.01.4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of The Use of Different Types and Levels of Tapioca Flour on The Physical Quality of Rabbit Meatballs

Abstract: The purpose of this research was to determine the best type and level of tapioca flour in rabbit meatballs based on pH, WHC, cooking loss, and color. Rabbit meat and tapioca flour were used as research materials. The method used is a laboratory experiment using a completely randomized design with a factorial pattern. Factor A is the type of tapioca flour, namely dragon tapioca flour and special tapioca flour. Factor B is the level of use of tapioca flour, namely 25% and 50%. The pH value, WHC, cooking loss, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…In a previous study, the water holding capacity of beef sausage with fortified duck egg shell flour decreased due to loss of protein during the cooking process [23]. Calcium can attract water molecules from within the material to form hydrates and the texture will also be more compact [31].…”
Section: Discussionmentioning
confidence: 95%
“…In a previous study, the water holding capacity of beef sausage with fortified duck egg shell flour decreased due to loss of protein during the cooking process [23]. Calcium can attract water molecules from within the material to form hydrates and the texture will also be more compact [31].…”
Section: Discussionmentioning
confidence: 95%
“…Starch added during meatball production can bind water which causes free water to enter the granule and bond with starch. This binding takes place during the heating or cooking process of the meatballs [19].…”
Section: Water Activity (Aw)mentioning
confidence: 99%
“…An effect of liming time on rambak quality parameters was also observed by other researchers. In [16] Widati et al compared four treatments with liming duration of 24, 48, 72 and 96 hours and found that the best result was achieved when using 96-hour treatment. The rambak crackers had the protein content 6.10%, water content 0.11%, calcium content 1.88%, volume expansion ratio 372.12%, crispness score 5.38 and taste score 6.89 [16].…”
Section: Note: Ns = Not Significantmentioning
confidence: 99%
“…At the time of boiling the skin, the water will be bound in the collagen protein forming a gel with a very strong bond so that at the time of drying it is difficult to evaporate it, but it can be removed at the time of frying due to the use of high temperatures [23]. The amount of water absorbed during cooking plays a role in conversion collagen into gelatin, and affects the level of the development and crispness of the rambak crackers produced [16].…”
Section: Volume Expansionmentioning
confidence: 99%